MECHANICAL PROPERTIES OF THREE-LAYERED PARTICLEBOARDS WITH FACE LAYERS OF BEECH AND OAK PARTICLES AND A CORE LAYER OF CONIFER AND SUNFLOWER STALKS PARTICLES - Grigorov, Rosen; Savov, Viktor (Innovation in Woodworking Industry and Engineering design, 2023)
The present study aims to establish the mechanical properties of three-layered particleboards with a face layer entirely from beech and oak particles. Three compositions of the panels were studied, with the corresponding content of the face layers as follows: 30%, 40% and 50%. To analyse the possibility of reducing the content of pinewood particles in the core layer, it is replaced with sunflower stalk particles with the participation of 30%, 40% and 50%. This research determined the effect of those factors on the main mechanical properties of particleboards. As a result of the study, it was found that the increase in the percentage of the face layers leads to a significant increase in the mechanical properties of the panels. It was found that by using the hardwood in the face layers of the panels, the share of this raw material can be increased to 50%, and sunflower stalks are a suitable raw material as an alternative raw material for the core layer of the particleboards